CRISPR-Cas13a system: A novel tool for molecular diagnostics - Zhao, Lixin; Qiu, Minyue; Li, Xiaojia; Yang, Juanzhen; Li, Jintao (Frontiers in Microbiology, 2022)
The clustered regularly interspaced short palindromic repeats (CRISPR) system is a natural adaptive immune system of prokaryotes. The CRISPR-Cas system is currently divided into two classes and six types: types I, III, and IV in class 1 systems and types II, V, and VI in class 2 systems. Among the CRISPR-Cas type VI systems, the CRISPR/Cas13a system has been the most widely characterized for its application in molecular diagnostics, gene therapy, gene editing, and RNA imaging. Moreover, because of the trans-cleavage activity of Cas13a and the high specificity of its CRISPR RNA, the CRISPR/Cas13a system has enormous potential in the field of molecular diagnostics. Herein, we summarize the applications of the CRISPR/Cas13a system in the detection of pathogens, including viruses, bacteria, parasites, chlamydia, and fungus; biomarkers, such as microRNAs, lncRNAs, and circRNAs; and some non-nucleic acid targets, including proteins, ions, and methyl groups. Meanwhile, we highlight the working principles of some novel Cas13a-based detection methods, including the Specific High-Sensitivity Enzymatic Reporter UnLOCKing (SHERLOCK) and its improved versions, Cas13a-based nucleic acid amplification-free biosensors, and Cas13a-based biosensors for non-nucleic acid target detection. Finally, we focus on some issues that need to be solved and the development prospects of the CRISPR/Cas13a system.